MATURATION OF JANDAÍRA BEE HONEY (Melipona subnitida DUCKE, 1910) AS A PRODUCT CONSERVATION STRATEGY (Environmental Smoke, 2024)
Native bees play an important role in environmental balance as they are the main pollinators of native forests and agricultural crops. During the pollination process, native bees collect nectar from flowers and transform it into a honey with medicinal properties, unique aroma, and flavor. The rational rearing of native bees (meliponiculture) has been developing and attracting interest in this important zootechnical activity. In this context, this study evaluated the maturation of Jandaíra bee honey (Melipona subnitida) as an alternative for preserving this highly valued honey. Samples of Jandaíra bee honey were stored in metallic-topped glass containers and kept in a dark environment. Weekly, the lids of the containers were loosened to release gases and then tightened again. After seven months, the samples were matured and no longer released gases when opened. At the end of the experiment, the product maintained its quality, safety, hygiene, and had a slightly acidic taste and pleasant aroma, which were appealing to consumers.